Progress in Artificial Intelligence Techniques: from Brain to Emotion - Tole Sutikno; Mochammad Facta; G.R. Arab Markadeh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Artificial Intelligence (AI) techniques, e.g. expert system (ES), fuzzy logic (FL), artificial neural network (ANN), genetic algorithm (GA), particle swarm optimization (PSO) and biologically inspired (BI) have recently been applied widely in power electronics and motor drives.Each AI method has its own uniqueness and characteristics. Recently, researchers have developed a computational model of emotional learning in mammalian brain, namely brain emotional learning based intelligent controller (BELBIC). The results indicate the ability of BELBIC to control unknown non-linear dynamic systems. Therefore, the BELBIC can be easily adopted for niche mechatronics and industrial applications.